Defect Analysis in the Aircraft Painting Process at PT XYZ using Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) Methods - Rasya, Shafira Maura; Fahma, Fakhrina (Performa: Media Ilmiah Teknik Industri, 2000)
PT XYZ is a company that is competent in the manufacturing of aircraft and helicopters. In the aircraft production process, an aircraft painting process is carried out in the Painting Shop hangar. Painting on aircraft serves a dual purpose: protecting the aircraft from rust and corrosion, and representing the identity of a company or country. However, many defects are still found during this process that do not meet quality standards. This can be seen from the aircraft painting final inspection defect data for 2020-2023, 307 defects were found from 5 painted aircraft. This research employs the Failure Mode and Effect Analysis (FMEA) to identify failure modes in defects, their causes, and the severity, occurrence, detection, and Risk Priority Number (RPN) values of these defects, thereby determining repair priorities. The types of defects, misses, and runs fall into the high-risk category because they have an RPN value of >200, so they will be prioritized for immediate improvement. Fault Tree Analysis (FTA) is also used to identify the root causes of defects that occur. The causes of defects are attributed to human, machine, method, and environmental factors.